Pengaruh Lingkungan Kerja, Disiplin Kerja, dan Kepuasan Kerja terhadap Kinerja Karyawan pada Dinas Kesehatan Kota Semarang - Prima Dwi Hastuti; Kasmari Kasmari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This final project is the result of a research test of how much influence the work environment, work discipline and job satisfaction have on employee performance carried out at the Semarang City Health Office as an object. The research method is quantitative through distributing questionnaires which are filled in directly by employees who are referred to as primary data. The population is 200 Health Office employees who get 73 respondents after applying the purposive sampling method with the Slovin formula. The data analysis technique applies Multiple Linear Regression. From the results of testing the hypothesis on employee performance partially it is known that the work environment has a significant positive effect, while work discipline and job satisfaction have an effect but not significant. In improving employee performance, the company is expected to be able to improve the three aspects above so that workers feel more comfortable when completing a job and feel satisfied with the work that has been completed by giving awards or rewards to employees who get achievements. Thus the expertise of workers can increase as expected. Keywords: Work Environment, Work Discipline, Job Satisfaction, Employee Performance